Changing livelihoods at India's rural–urban transition. (October 2021) - Choithani, Chetan; van Duijne, Robbin Jan; Nijman, Jan
Highlights: India is experiencing a major employment shift out of agriculture, affecting the livelihoods of millions of people. This shift parallels substantial urban growth in hitherto rural regions but with few new local livelihood opportunities. Labor migration is an important alternative, with traditional seasonal migration replaced by permanent circular migration. Domestic migration is disproportionately undertaken by poor households; those with international migrants do much better. A strong pro-active policy stance is needed to simultaneously stimulate local livelihoods and facilitate labor migration. Abstract: In India, the past couple of decades witnessed, simultaneously, a massive shift of employment out of agriculture, substantial urban growth in heretofore rural regions, and rapid increases in the rates of labor migration. But very little is known about new livelihoods being forged or the whereabouts of these livelihoods. We draw on extensive primary data collected at two sites in West Bengal and Bihar, along with a comprehensive analysis of population census and GIS data, to investigate livelihood transformations and household well-being. We observe large-scale change, exceeding common perceptions of academics and policy makers. While the shift out of agriculture is momentous, alternative local livelihoods are scarce and, more than ever, labor migration offers a way out for many households. Traditional seasonal migration has made way for more permanent forms of circular labor migration. Our comparative study shows that the timing and nature of this transformation varies to some extent across India as the decline in agricultural employment occurred at different times. We also observe significantly different impacts of domestic versus international labor migration. There is a pressing need for pro-active government policies that stimulate local economic restructuring and livelihood opportunities and, as long as these local economies are insufficiently developed, that facilitate circular labor migration.